The Provison of Leaflet Media, Videos, and PowePoint on Hygiene Sanitation in Food Presentation to Increase Knowledge (Case Study on Traders in East Telukjambe District) - Medina Alya Andrifni; Ratih Kurniasari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Food poisoning can occur if traders do not pay attention to hygiene and sanitation in the food they sell. Good selling facilities and environment must comply with hygiene and sanitation standards, the place must have layout, floors, strong walls, adequate ventilation, adequate lighting, strong roof, and ceiling free from insects and vectors bully. Objective: The purpose of this study was to determine the effect of giving leaflets, videos, and PowerPoint media on sanitation hygiene in food serving in increasing the knowledge of traders in Telukjambe Timur Karawang District. Method: This type of research is Quasi Experimental with the Pre-Posttest Group Design research design. In this study, it was divided into 3 groups, namely the leaflet, video, and powerpoint group and was carried out on 1-6 May 2023. The population in this study were roadside food vendors in Telukjambe Timur Karawang District with a total sample of 45 subjects selected purposively. sampling. Measurement of pretest and posttest knowledge used a questionnaire with 14 questions and then analyzed the data using the Paired t-test because the data from the three media were normally distributed. Result: The results in this study were that the p-value on leaflet media was 0.582 (>0.05), on video media was 0.017 (<0.05), and on PowerPoint media was 0.023 (<0.05). Conclusion: The conclusion in this study is that there is an influence on increasing the knowledge of roadside traders regarding sanitation hygiene in presentations using video and powerpoint media. Whereas in the leaflet media there is no effect on increasing the knowledge of traders.